Tree-Shaped Flow Structures Viewed from the Constructal Theory Perspective - Miguel, A. F. (2012)
Constructal theory, conceived by Adrian Bejan, is the view that the generation of configuration in nature is a universal phenomenon, which is covered by a law of physics-the constructal law. This chapter addresses the generation of tree-shaped design in the light of constructal theory. First, we briefly review the constructal theory that is applicable to animate and inanimate flow systems. Next, we review the studies that are focused on the constructal view of tree-shaped flow structures. The constructal theory presented in this chapter introduces a new paradigm that is universally applicable in nature, engineering and social sciences.